2022
DOI: 10.1590/fst.111221
|View full text |Cite
|
Sign up to set email alerts
|

Zingiber officinale attenuates 6-hydroxydopamine induced oxidative stress and apoptosis through AKT, Nrf2, MAPK, NF-κB signaling pathway in PC12 cells

Abstract: To explore the protective impact of the ginger root ethanol extract (GRE) against the oxidative stress induced by 6-hydroxydopamine (6-OHDA) and apoptotic and its mechanism. Parkinson's disease (PD) model was established using 6-OHDA in the cells of rat adrenal pheochromocytoma (PC12). The GRE pretreatment increased PC12 cell viability of injury induced by 6-OHDA. The GRE effectively suppressed 6-OHDA-induced death, apoptosis through decreased Bax and cleaved-caspase 3 expression, and up-regulated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Ginger also increased erythroid-2-related factor 2 (Nrf2) gene expression and decrease nuclear factor kappa (NFkB) in animal testis [14]. Nrf2 have to regulate antioxidant molecule and enzyme and isolated in cytoplasm in general condition [17]. Ginger has multiple bioactive compounds including 6-gingerol, 6-shogaol, gingerdions, gingerdiol, paradols, 6-dehydrogingerols, 12-gingerol, and etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginger also increased erythroid-2-related factor 2 (Nrf2) gene expression and decrease nuclear factor kappa (NFkB) in animal testis [14]. Nrf2 have to regulate antioxidant molecule and enzyme and isolated in cytoplasm in general condition [17]. Ginger has multiple bioactive compounds including 6-gingerol, 6-shogaol, gingerdions, gingerdiol, paradols, 6-dehydrogingerols, 12-gingerol, and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent research showed that ginger can inhibit apoptosis and oxidative stress in PD model (6-OHDHA-indiced PCl12 cells). Reduction of stress oxidation sees thorough enhancement of antioxidant activity such as catalase, SOD, and another important marker [17].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain homeostasis, they are mostly eliminated by defense mechanisms, such as the antioxidant defense system, which includes glutathione peroxidase (GPx) catalase (CAT), and superoxide dismutase (SOD) (Wang, 2022;Jóźwiak & Politycka, 2019). However, when the rate of ROS generation exceeds that of elimination, homeostasis is perturbed, resulting in cellular damage and the loss of normal function, which can cause diseases like arteriosclerosis and cardiovascular disease as well as accelerated aging (Wilmes et al, 2020;Hao et al, 2022). Therefore, in-depth research on various methods for efficient ROS regulation is ongoing, especially focusing on natural bioactive compounds or secondary metabolites with antioxidant activity, which can activate antioxidant enzymes (Donadio et al, 2021;Setyorini & Antarlina, 2022).…”
Section: Introductionmentioning
confidence: 99%